2022
DOI: 10.3389/fonc.2022.920709
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of brigatinib in ALK-positive non-small cell lung cancer treatment: A systematic review and meta-analysis

Abstract: BackgroundBrigatinib is a central nervous system-active second-generation anaplastic lymphoma kinase (ALK) inhibitor that targets a broad range of ALK rearrangements in patients with non-small cell lung cancer (NSCLC). The current study aimed to analyze the pooled effects and adverse events of brigatinib in patients with ALK-positive NSCLC.MethodsThe pooled estimates and 95% confidence intervals (CI) were calculated with DerSimonian-Laird method and the random effect model.ResultsThe pooled objective response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Brigatinib (BGT) is a tyrosine kinase inhibitor that has shown excellent activity against non‐small cell lung cancer. [ 125 ] In order to achieve a prolonged therapeutic effect, a recent study by Ahmed and teammates reported BGT‐loaded sustained‐release ethyl cellulose NSs for the treatment of non‐small cell lung cancer. [ 126 ] The developed BGT@NSs exhibited a particle size of 261.0 ± 3.5 nm (PDI: 0.301) along with a zeta potential of −19.83 ± 0.06 mV.…”
Section: Nanosponges For the Treatment Of Cancermentioning
confidence: 99%
“…Brigatinib (BGT) is a tyrosine kinase inhibitor that has shown excellent activity against non‐small cell lung cancer. [ 125 ] In order to achieve a prolonged therapeutic effect, a recent study by Ahmed and teammates reported BGT‐loaded sustained‐release ethyl cellulose NSs for the treatment of non‐small cell lung cancer. [ 126 ] The developed BGT@NSs exhibited a particle size of 261.0 ± 3.5 nm (PDI: 0.301) along with a zeta potential of −19.83 ± 0.06 mV.…”
Section: Nanosponges For the Treatment Of Cancermentioning
confidence: 99%